Primary Care Workforce Shortages and Career Recommendations From Practicing Clinicians. (May 2015) - DesRoches, Catherine M.; Buerhaus, Peter; Dittus, Robert S.; Donelan, Karen
<x xml:space="preserve">Abstract</x> Purpose The success of efforts to bolster the primary care workforce rests in part on how these clinicians view their professions and their willingness to recommend their careers to others. The authors sought to examine career and job satisfaction, perceptions of workforce shortages, and willingness to make career recommendations among primary care physicians (PCPs) and primary care nurse practitioners (PCNPs). Method In 2012, the authors mailed a national survey concerning the issues above to 1, 914 randomly chosen clinicians found on national databases: 957 PCPs and 957 PCNPs. Results A total of 972 eligible clinicians (505 PCPs, 467 PCNPs) returned the survey. Using standard opinion research procedures, the authors estimated there were approximately 1, 589 eligible clinicians in their sample (response rate, 61.2%). PCNPs and PCPs were more likely to recommend a career as a PCNP than as a PCP, despite the perception among all clinicians of a serious shortage of PCPs nationally and in their own communities. This finding held among PCNPs who reported low workplace autonomy and among PCPs reporting that they were satisfied with their own careers. Conclusions Efforts to solve the primary care workforce shortage that ignore the significant dissatisfaction of PCPs with their own careers are unlikely to be successful. Simply adding training slots and increasing reimbursement rates will do little to solve the problem if PCPs continue to view their own careers as ones they cannot recommend to others.